Estação de cultivo baseada na precipitação pluvial diária e na ocorrência de períodos secos para a região de Rio Largo, Alagoas. - Carvalho, André Luiz de (2010)
The objective of this study was to determine the characteristics of the growing season and dry spells based in daily rainfall data in Rio Largo, Alagoas. A serie time with 36 years of daily precipitation data (1973 - 2008) was measured in the conventional station (9 ° 28'S 35 ° 49'W, 127m) of the Agricultural Science Center (ASC) of the Federal University of Alagoas (FUA). In the definition of dry days were used six different values of precipitation (0, 1, 2, 3, 4 and 5 mm). The day was considered dry when it has a rainfall of less than one of these six values and it was defined as wet if the rainfall w as higher. The dry periods were defined as the sequence of dry days with precipitation less than or equal to the reference value of precipitation. The beginning (potencial and success), end e length of the rainy season and cultivation were measured by using direct methods. Statistical analysis of rain occurrence and dry spell was done with Markov chain in the software Instat Climatic. The dry periods were defined in three different intervals (≥ 5 days, ≥ 7 days and ≥ 10 days). At 80% probability the rainy season began on April 7th and finished on October 24th with length of 221 days. The beginning of the rainy season was anticipated in La Niña years (10 days) and delayed in years of El Niño (9 days), and consequently, cause a decrease in length of growing season for El Niño years and increase in La Niña years. The highest occurrences of rainy days were observed between April to August (50 to 90%). And November was the driest month (65 to 97%). In the rainy season (March to August) the dry spell of 5 days was the one that had the greatest chance of occurrence (5 to 85%). The occurrence of dry spells was low for 7 days (0 to 45%) and 10 days (0 to 5%). The occurrences of dry spells were intensified by the occurrence of El Niño events (1 to 60%) between 1980 and 1983 and were reduced in years of La Niña events (0 to 45%) between 1983 and 1985.